Multiresistance in Escherichia coli associated with Extended Spectrum Beta-lactamases in urine cultures obtained in patients from a province of the Peruvian Amazon - Tamayo-Contreras, Héctor Luis (2021)
Background: Beta-lactam antibiotics are the most used in the treatment of urinary infections in Peru. Bacterial resistance is frequently produced by the presence of Extended Spectrum Betalactamases (ESBL) in Enterobacteriaceae. Objective: To determine the multi-resistance in E. coli associated to extended spectrum beta-lactamases in urine cultures from adults residing in the province of Tambopata-Madre De Dios. The study: Non-experimental, descriptive study, detection and confirmation of ESBL was performed with the double disc technique using ceftazidime, cefotaxime, cefepime, aztreonam and amoxicillin plus clavulanic acid. Microbial resistance and susceptibility was identified using the diffusion disk technique. Findings: 162 strains of E. coli were isolated. Strains with resistance to the antibiotics ampicillin (71%), trimethoprine sulfamethoxazole (49%), ciprofloxacin acid (37%), nalidixic acid (37%) and aztreonam (31%) were identified. Conclusion: There is antimicrobial resistance mediated by ESBL-producing strains of E. coli.